Delayed post-traumatic presentation of severe sternal osteomyelitis: A strong multidisciplinary effort and a novel reconstruction technique for a challenging case. (June 2020) - Tamburrini, Alessandro; Ahmed, Hanad; Talbot, Thomas; Harrison, Oliver; Khan, Mansoor; Tilley, Simon; Alzetani, Aiman
Abstract: Sternal osteomyelitis is a morbid and challenging condition, which can rarely occur after trauma, with no established consensus over best therapeutic options. In this case, a 47-year-old man with history of intravenous drug use presented 11 weeks after a minor blunt chest trauma with a severe necrotizing osteomyelitis involving sternum, muscles, fascia and subcutaneous tissue and positive blood cultures for Methicillin Sensitive Staphylococcus aureus . Alongside tailored antibiotic therapy, extensive surgical debridement was performed, leaving a full thickness 3 × 4 cm sternal defect and a large skin defect. After 4 weeks of antibiotics and Vacuum-Assisted-Closure pump, a novel reconstruction technique was utilized, with full collaborations of thoracic surgeons, orthopaedic surgeons and plastic surgeons. An autologous tricortical iliac crest bone graft was harvested and shaped to fit the full-thickness sternal defect, while two titanium sigmoid-shaped clavicle plates were used for internal fixation of the autograft. The large skin defect was covered with a pedicled myocutaneous latissimus dorsi flap. Integrity and stability of the chest wall was fully restored, and infection was completely eradicated. No complications occurred and the patient was well at the 18 months follow-up. To the best of our knowledge, this is the first report on autologous iliac crest bone graft in the treatment of sternal osteomyelitis. In this case, it proved to be a viable therapeutic option, providing good long-term clinical and cosmetic results.